Antioxidant mechanism of tea polyphenols and its impact on health benefits - Yan, Zhaoming; Zhong, Yinzhao; Duan, Yehui; Chen, Qinghua; Li, Fengna (Animal Nutrition, 2020)
Tea trees have a long history of cultivation and utilization. People in many countries have the habit of drinking tea and choosing green tea, oolong tea, or black tea according to different regions and personal tastes. Tea polyphenols are a general term for polyphenol compounds in tea, and has been shown to have good effects on antioxidant, anti-inflammatory, cancer prevention and regulation of lipid metabolism. Tea polyphenols have been widely used as antioxidants in disease treatment and animal husbandry, but their specific mechanism of action needs to be further clarified and revealed. This review focuses on the definition, classification, antioxidant activity and the regulation of signaling pathways of tea polyphenols. This paper also aims to examine the application of tea polyphenols in human and animal health, providing a scientific basis for this application in addition to proposing future directions for the development of this resource.